2012
DOI: 10.1093/ejcts/ezs266
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid valve repair: is ring annuloplasty superior?†

Abstract: Patients who require TV surgery either as an isolated or a combined procedure constitute a high-risk group. The long-term survival is poor. Tricuspid valve repair with a ring annuloplasty is associated with improved survival and a lower reoperation rate than that with a suture annuloplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 16 publications
2
48
0
5
Order By: Relevance
“…3 Despite improved understanding of FTR and its surgical management, reports of late survival associated with FTR are limited. Guenther et al showed that 10-year survival after tricuspid annuloplasty (TAP) was 46%, 4 and Pfannmuller et al showed that 5-year survival was approximately 60%. 5 Persistent FTR after mitral prosthetic replacement is reported to be a risk factor for postoperative congestive heart failure and late mortality.…”
Section: Methodsmentioning
confidence: 99%
“…3 Despite improved understanding of FTR and its surgical management, reports of late survival associated with FTR are limited. Guenther et al showed that 10-year survival after tricuspid annuloplasty (TAP) was 46%, 4 and Pfannmuller et al showed that 5-year survival was approximately 60%. 5 Persistent FTR after mitral prosthetic replacement is reported to be a risk factor for postoperative congestive heart failure and late mortality.…”
Section: Methodsmentioning
confidence: 99%
“…Существует немало работ, посвященных сравнению эф-фективности данных хирургических подходов, основным критерием оценки которой является появление возврат-ной ТР в отдаленном послеоперационном периоде [12, 16-18, 20, 24]. Все виды вмешательств демонстрируют удовлетворительные непосредственные результаты, обе-спечивая хорошую замыкательную функцию ТК, однако показатели свободы от реопераций в отдаленном периоде существенно выше при использовании опорных колец (83-94,8% против 39-87,9% при шовной пластике), что позволяет считать имплантационные методики наиболее эффективным способом коррекции ФНТК [12,24].…”
Section: таблица 2 динамика показателей эхокг после хирургической коunclassified
“…FTR is primarily treated with a valve reconstruction that carries a much lower operative risk than valve replacement [15,25]; however, there is still a heated debate regarding the superior method of repair (either suture based or a prosthetic ring annuloplasty). McCarthy [26] reported that both flexible bands and rigid planner rings had much less recurrent TR than the De Vega procedures.…”
Section: Tablementioning
confidence: 99%
“…Tricuspid valve replacement, which allows adequate surface area of co-aptation impossible, is associated with higher mortality [13,14]. Several studies have shown better long-term freedom from recurrent TV regurgitation and repeat operation in those who underwent TV repair [15][16][17][18][19][20]; however, data regarding the outcome of such an approach and the optimal surgical technique for TV repair is lacking [6,21]. …”
Section: Introductionmentioning
confidence: 99%